ANALYSIS OF STUDENT MINI-RESEARCH REPORT ON THE DEVELOPMENT OF TEACHER COMPETENCE IN THE DIGITAL ERA - Satriyawan, Aziz Nuri; Sriyanto, Agus; Rohmawati , Nur Maya; Priyani , Galih; Farihah, Elyaum; Yudhiarti, Ndaru Putri (PIONIR: JURNAL PENDIDIKAN, 2026)
This study analyzes student mini-research reports on teacher competency development in the digital era. The objectives of the study include reviewing mini-research activities to identify teacher competency development amidst digital transformation, both in terms of challenges and needs. The research method used is a descriptive qualitative approach and examines mini-research reports compiled by students with an assessment rubric. The research subjects were 14 PGMI Semester V students divided into 5 groups. Data collection used observation, interviews and documentation of student mini-research reports. The results of the study are that: 1) students are able to identify gaps in teacher competency in mastering learning technology, digital literacy and digital pedagogy, 2) through the reports compiled by students, it reveals the need for teacher quality in designing innovative technology-based learning according to student needs, 3) and mini-research activities provide references for the development of teacher competency on an ongoing basis. The research conducted contributes to studying contemporary educational issues and produces data to develop teacher quality in the digital era. This study sharpens the foundation regarding teacher competency in the digital era and opens opportunities for further research in terms of mastering technology-based learning, digital literacy and digital pedagogy. Keywords: Student Mini-Research, The Digital Era, Teacher Competence